EFEKTIVITAS MODIFIED COLABORATIVE STRATEGIC READING DALAM READING CLASS ACTIVITY - Putu Ayu Paramita Dharmayanti; Dewa Ayu Ari Wiryadi Joni (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2014)
The study aimed at improving the students’ reading comprehension by implementing Modified Collaborative Strategic Reading (MCSR) technique. The subject was grade eleven students of SMA (SLUA) Saraswati 1 Denpasar, in which the amount was thirty students. There were two cycles (eight meetings), in this Classroom based Action Research. There were three instruments used: test, questionnaire, and diary. From the result of the post-test and analyzed questionnaire, it is shown that there is an increase in every meeting. This can be concluded that MCSR is effective in improving the students’ reading comprehension.